Changes in chemical interactions and gel properties of heat-induced surimi gels from silver carp (Hypophthalmichthys molitrix) fillets during setting and heating: Effects of different washing solutions. (February 2018) - Zhang, Longteng; Li, Qian; Shi, Jing; Zhu, Beiwei; Luo, Yongkang
Abstract: The present study aimed to evaluate different washing solutions [distilled water, CaCl2 (0.1% and 0.2%, w/v), and MgCl2 (0.1% and 0.2%, w/v)] on chemical interactions and gel properties of surimi gels derived from silver carp ( Hypophthalmichthys molitrix ) fillets during setting and heating. Besides, changes in protein profiles were analyzed by SDS-PAGE. CaCl2 and MgCl2 washing increased the contents of calcium and magnesium in washed surimi pastes. During the gelation process, changes in chemical linkages occurred in all groups, which brought the increases in hydrophobic interactions and the decreases in ionic bonds and sulfhydryl groups. Hydrophobic interactions contributed more in the gel-forming than other non-covalent bonds. Ca 2+ and Mg 2+ washing significantly ( P  < 0.05) enhanced the aggregation of the myosin heavy chain (MHC) and the formation of hydrophobic interactions, which led to better water-holding capacity, whiteness, breaking force, and gel strength. Moreover, variations in chemical interactions were strongly correlated to gel properties across different washing processes, especially for hydrogen bonds. In terms of the enhancement of gel properties, washing with 0.2% CaCl2 could bring high value when applied to the aquatic industry. Graphical abstract: Highlights: 0.2% CaCl2 and 0.2% MgCl2 washing exhibited better gel properties. Ca 2+ and Mg 2+ washing promoted the formation of hydrophobic interactions. Ca 2+ and Mg 2+ washing accelerated MHC aggregation during setting. Hydrophobic interactions are the main chemical linkages in gelation process. Gel properties were highly correlated to chemical interactions.